Interferon γ treatment increases endocannabinoid and related N‐acylethanolamine levels in T84 human colon carcinoma cells. (5th February 2018) - Alhouayek, Mireille; Rankin, Linda; Gouveia‐Figueira, Sandra; Fowler, Christopher J
Abstract : Background and Purpose: Endocannabinoids and related N ‐acylethanolamines (NAEs) are involved in regulation of gut function, but relatively little is known as to whether inflammatory cytokines such as IFNγ affect their levels. We have investigated this in vitro using cultures of T84 colon cancer cells. Experimental Approach: T84 cells, when cultured in monolayers, differentiate to form adult colonic crypt‐like cells with excellent permeability barrier properties. The integrity of the permeability barrier in these monolayers was measured using transepithelial electrical resistance (TEER). NAE levels were determined by ultra‐performance liquid chromatography‐tandem mass spectrometric analysis. Expression of the enzymes involved in NAE and 2‐arachidonoylglycerol (2‐AG) turnover were assessed with qPCR. Key Results: IFNγ treatment for 8 or 24 h increased levels of both endocannabinoids (anandamide and 2‐AG) and the related NAEs. The treatment did not affect the rate of hydrolysis of either anandamide or palmitoylethanolamide by intact cells, and in both cases, fatty acid amide hydrolase (FAAH) rather than NAE‐hydrolysing acid amidase (NAAA) was mainly responsible for the hydrolysis of these NAEs. IFNγ treatment reduced the TEER of the cells in a manner that was not prevented by inhibition of either FAAH or NAAA but was partially reversed by apical administration of the NAE palmitoylethanolamide. Conclusion and Implications: IFNγ treatment mobilized endocannabinoid and related NAE levels in T84 cells. However, blockade of anandamide or NAE hydrolysis was insufficient to negate the deleterious effects of this cytokine upon the permeability barrier of the cell monolayers. Linked Articles: This article is part of a themed section on 8 th European Workshop on Cannabinoid Research. To view the other articles in this section visithttp://onlinelibrary.wiley.com/doi/10.1111/bph.v176.10/issuetoc